Surface and sub-surface modification on Ni based superalloys - Mithal, Abeer (2017)
Nickel superalloys are strong, tough metallic materials, that are widely used in heavy duty machinery. Many mechanical treatment process are carried out on them, prior to use, to further improve their strength, especially for safety critical applications. This project investigated the impact of mechanical surface treatment on the material properties of Udimet 720 Li- a nickel superalloy. In order to meet its aims, this project was divided into two parts. The first part attempted to experimentally analyse the effect of laser shock peening (LSP), on the material- specifically on hardness, compressive residual stresses, surface roughness, corrosion resistance and wear resistance. The effect of laser power density on the LSP process was also studied. The second part of the project attempted to numerically model shot peening on the same material. Shot peening is a universally known surface enhancement technique which is already employed in industry, however prediction of shot peened material properties is still a challenge due to the many parameters involved. This project attempted to analyse the shot peening process numerically, to enable better understanding and predictability. It was found that LSP was capable of improving material hardness although the residual stresses developed were not very significant. It was also found that the corrosion resistance and wear resistance were greatly impacted by the LSP process and that surface roughness could be improved under certain conditions. A dynamic, non-linear, multiple impingement numerical model for shot peening was also developed using elastic-plastic hardening and a strain rate dependent material constitutive model. The model showed reasonable correlation with experimental results.